Disease Situation in Indian forests. I. Stem Diseases of Some Exotics Due to Cortlcium Salmonlcolor & Monochaetia unicornis - Bakshi, B. K.; Ram Reddy, M. A.; Singh, Sujan; Pandey, P. C. (Indian Forester, 1970)
Two damaging stem diseases on exotics are reported. They are the pink disease due to Corticium salmonicolor resulting in over 50 per cent mortality in 2-5 year plantations of Eucalyptus globulus in North Bengal. The fungus is also responsible for the serious twig blight in Populus casale, Casuarina montana and Podocarpus glacilior at New Forest, Dehra Dun. A serious oozing canker on stems and branches resulting in die back on 3 species of exotic cypress (Cupressus arizonica. C lusitanica and C. sempervirens) and Juniper (Jumperus procera) in New Forest is caused by Monochaetia unicornis, a new record in India. The causal organisms, hosts attacked, damage, factors predisposing plants to attack by the pathogens and control measures are described.